Cost Reduction Analysis : Tools and Strategies. - Bragg, Steven M. (Wiley advisor., 2010)
Discover the tools for knowing the costs your company should cut, without impacting its ability to deliver goods and services. New from Steve Bragg, this book provides the tools for determining which costs a company should cut, without impacting its ability to deliver goods and services. It explains how to use throughput analysis in order to locate bottleneck operations in a company, which in turn dictates where capital investments should (and should not) be made. Delves into process analysis, to determine where excess resources are being used in a business process -- Describes the total cost of ownership, showing how a single purchasing decision actually snowballs into a variety of ancillary costs -- Shows how to create and use a spend management system to reduce procurement costs -- Shows how just-in-time systems can be used to eliminate inventory costs. Cost Reduction Analysis: Tools and Strategies provides examples to show how much cost can potentially be eliminated to avoid drastic action later that can imperil your corporation's direction and future. – Provided by publisher.